Determinan Pajanan Pestisida Terhadap Kadar Haemoglobin Wanita Usia Subur (WUS) di Kecamatan Dempo Selatan Pagar Alam - Purba, Imelda; Ningrum, Rafika Oktiva; Saci, Muhammad Amin Arigo (LPPM Hang Tuah Pekanbaru, 2024)
Women of childbearing age (WCA) are important in the agricultural sector. The farming activities allow women of childbearing age to come into contact with pesticides. Women of childbearing age are at risk of experiencing health effects, one of which is anemia, due to exposure to pesticides. The study aimed to analyze the determinants of pesticide exposure to the blood Hb levels of WCA. This type of research is quantitative analytic with a cross-sectional study approach. The population of this study was WCA, which was exposed to pesticides in the South Dempo District of Pagar Alam. The sample size of this study was 120 women, who were taken using the cluster sampling technique. Data was collected using an interview method using a questionnaire, observation using a checklist, measurement of body weight using a weight scale, height using microtoise, and Hb level using Easy Touch GCHB. Data analysis of the study's results was carried out univariately and bivariate using the Chi-Square statistical test. The results of measuring blood Hb levels showed 39 people (32.5%) with abnormal Hb levels and 81 respondents (67.5%) with normal Hb levels. The bivariate analysis results showed that the variables associated with blood Hb levels of WUS were the duration of washing of spraying clothes (p=0.037) and the duration of preparing pesticides (p=0.037). In Contras, the variables that are not associated with blood Hb levels were the duration of spraying, the duration of mixing, the frequency of spraying, and the use of PPE. It was recommended that women of childbearing age reduce the length of time spent washing and spraying clothes and preparing pesticides through good time management.